[OP.2C.06] OPTIMAL BLOOD PRESSURE GOAL FOR THE ELDERLY CHINESE: THE FINDINGS FROM THE NORTHERN SHANGHAI STUDY. (September 2017) - Teliewubai, J.; Zhang, Y.; Lu, Y.; Bai, B.; Yu, S.; Zhou, Y.; Chi, C.; Xiong, J.; Xu, Y.
Abstract : Objective: The Eighth Joint National Committee Panel recommended novel blood pressure (BP) goals for individuals with hypertension, which is still under debate. We therefore assessed patients' target organ damages in controlled hypertensives defined by the Seventh or Eighth Joint National Committee thresholds (JNC7 and JNC8) in a community-based elderly Chinese population, in order to find the optimal BP goal for the elderly Chinese. Design and method: 1599 community-based elderly participants (age >65 years old) were recruited in the northern Shanghai. Participants were classified by chronic kidney disease (CKD) or diabetes mellitus (DM) to investigate the conditions of their BP control based on both the JNC7 and JNC8. Then participants were categorized into 4 groups: normotensive individuals (Group1), individuals at BP goal by JNC7 (Group2), individuals at BP goal by JNC8 but not by JNC7 (Group3), and individuals not at goal by both guidelines (Group4). Patients' hypertensive target organ damages as left ventricular mass index (LVMI), peak transmitral pulsed Doppler velocity / early diastolic tissue Doppler velocity (E/Ea), pulse wave velocity (PWV), carotid intima-medium thickness (CIMT), urinary albumine-creatinine ratio (UACR) and estimated glomerular filtration rate (eGFR) were evaluated. Results: According to the JNC7, 48.5% of the entire population were at BP goal, while 67.5% were at-goal by the JNC8, including 19.0% reclassified as at-goal. Group4 had significantly greater LVMI than the group2 (96.5 vs 91.5 g/m 2, p < 0.05), and also had significantly greater E/Ea (10.3 vs 9.7 and 10.3 vs 9.7, p < 0.05) and PWV (10.3 vs 9.3 m/s and 10.3 vs 9.7 m/s, p < 0.05) than both the group2 and group3, however, there were no significantly differences of these variables between group2 and group3. Conclusions: In the community-based elderly Chinese, 32.5% of the entire population remained uncontrolled BP by JNC8, but 19% were reclassified as at-goal. The reclassified group did not have more target organ damages than the original at-goal group, so BP criteria by JNC8, but not by JNC7, would be more beneficial for the elderly Chinese. Figure. No caption available.